A reduction in chronic hepatitis B virus infection prevalence among children in Vietnam demonstrates the importance of vaccination - Nguyen, Tran Hien (Vaccine, 2013)
BACKGROUND: Vietnam has high endemic hepatitis B virus infection with >8% of adults estimated to have chronic infection. Hepatitis B vaccine was first introduced in the national childhood immunization program in 1997 in high-risk areas, expanded nationwide in 2002, and included birth dose vaccination in 2003. This survey aimed to assess the impact of Vietnam’s vaccination programme by estimating the prevalence of hepatitis B surface antigen (HBsAg) among children born during 2000–2008. METHODS: This nationally representative cross-sectional survey sampled children based on a stratified three-stage cluster design. Demographic and vaccination data were collected along with a whole blood specimen that was collected and interpreted in the field with a point-of-care HBsAg test. RESULTS: A total of 6,949 children were included in the survey analyses. The overall HBsAg prevalence among surveyed children was 2.70% (95% confidence interval (CI): 2.20–3.30). However, HBsAg prevalence was significantly higher among children born in 2000–2003 (3.64%) compared to children born 2007–2008 (1.64%) (prevalence ratio (PR: 2.22, CI 1.55–3.18)). Among all children included in the survey, unadjusted HBsAg prevalence among children with ≥3 doses of hepatitis B vaccine including a birth dose (1.75%) was significantly lower than among children with ≥3 doses of hepatitis B vaccine but lacked a birth dose (2.98%) (PR: 1.71, CI: 1.00–2.91) and significantly lower than among unvaccinated children %) (PR: 1.99, CI: 1.15–3.45). Infants receiving hepatitis B vaccine >7 days after birth had significantly higher HBsAg prevalence (3.20%) than those vaccinated 0-1 day after birth (1.52%) (PR: 2.09, CI: 1.27–3.46). CONCLUSION: Childhood chronic HBV infection prevalence has been markedly reduced in Vietnam due to vaccination. Further strengthening of timely birth dose vaccination will be important for reducing chronic HBV infection prevalence of under 5 children to <1%, a national and Western Pacific regional hepatitis B control goal.